2015
DOI: 10.1007/s12263-015-0497-8
|View full text |Cite
|
Sign up to set email alerts
|

GABA selectively increases mucin-1 expression in isolated pig jejunum

Abstract: The inhibitory neurotransmitter GABA (γ-aminobutyric acid) is synthesized by glutamic acid decarboxylase, which is expressed in the central nervous system and in various other tissues including the intestine. Moreover, GABA can be ingested in vegetarian diets or produced by bacterial commensals in the gastrointestinal tract. As previous studies in lung have suggested a link between locally increased GABA availability and mucin 5AC production, the present study sought to test whether the presence or lack of GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…As expected, the lowest pH was found in the digesta fluid of the stomach (4.1±0.3, average pH of N=6), whereas the jejunum appeared to have the highest pH (6.5±0.1), decreasing again in the cecum (6.0±0.2, see additional file 1). These findings are very much in line with the results of our previous study ( Braun et al, 2015 ): highest concentrations of GABA were found in the stomach whereas the lowest GABA concentration was detected in the jejunum, increasing again towards the hindgut.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, the lowest pH was found in the digesta fluid of the stomach (4.1±0.3, average pH of N=6), whereas the jejunum appeared to have the highest pH (6.5±0.1), decreasing again in the cecum (6.0±0.2, see additional file 1). These findings are very much in line with the results of our previous study ( Braun et al, 2015 ): highest concentrations of GABA were found in the stomach whereas the lowest GABA concentration was detected in the jejunum, increasing again towards the hindgut.…”
Section: Resultssupporting
confidence: 92%
“…In accordance with our recent hypothesis that GABA levels influence mucin-1 expression, McGuckin, Linden, Sutton and Florin (2011) described that the mucus layer is thickest in the stomach and colon. Apparently this does not only correlate with the number and distribution of mucus-producing cells throughout the gastrointestinal tract but also with our finding that GABA levels are highest in the stomach and colon ( Braun et al, 2015 ). These GABA levels were derived from the same animals and correlate well with measured pH levels.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The TGX Stain-Free TM FastCast TM Kit (Bio-Rad) was used to prepare 10% SDS-PAA gels. Protein detection with this technique is based on trihalo-compound modification of tryptophan residues and has proven to be superior to the conventional detection of housekeeping-proteins [ 68 70 ]. Loaded protein amounts were as described previously and gels for the detection of total and phosphorylated Erk1/2 were run in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…Braun et al. also mentioned that such enzyme could promote mucin expression . Phosphoinositide phospholipase C (Plch1) is an enzyme that cleaves phosphatidylinositol 4,5‐bisphosphate to generate inositol 1,4,5‐trisphosphate and diacylglycerol.…”
Section: Discussionmentioning
confidence: 99%